Demonstrativos na România nova: Espanhol de Lima e espanhol de Buenos Aires - Clarice Soares França Silva (2013)
This work is descriptive and it is based on the Variationist and Functionalist perspectives to study the functioning of the demonstratives in Spanish spoken in Lima and Buenos Aires, based on NURC project data. CAMBRAIA & BIANCHET (2008) state that some Romance languages have a tendency to transform a ternary system into abinary system. This adaptation has to be understood so that the new rules that are governing the system can be established. With this purpose, we rely on the GONZÁLEZ ÁLVAREZ (2006) classification system to develop our own classification system to test four hypotheses, namely: a) the choice of demonstratives forms is sensitive to the function the demonstratives complies in the sentence, as identified byGONZÁLEZ ÁLVAREZ (2006) for Mexican Spanish, being possible to identify common patterns for the variants of the American Spanish; (b) the demonstrative system of the Spanish of Lima and Buenos Aires have a tendency to become binary, disappearing aquel with the enforcement of ese, as has been seen by some authors for Latin American Spanish, like CAMBRAIA (2009, 2012) and STRADIOTO (2012) on the Mexican Spanish; (c) the process to become binary of the Lima and Buenos AiresSpanish demonstrative system should involve variation between forms, because the changes are preceded by linguistic variation between competing forms, as pointed out by LABOV (1972, 1995, 2001); and (d) given the similarity between different varieties of Latin American Spanish, the grammaticalized use should be present in Buenos Aires,as suggested by the COLANTONI (2000) study, and also in the Lima data.It was found that the studied two systems present mainly binary patterns, having the second person form broad scope, with roles usually assigned to other forms, and existing a low occurrence of the form of the third person. The use of forms is governed by their functions in discourse and, although, for some functions there are some categorical uses to the first or second person, for other functions, it was identified a variation process, with two or three coexisting forms for the same function established by our rating system. In both varieties, Lima Spanish and Buenos Aires Spanish, it was observed the use of masculine first person singular with the grammaticalized use, but in Buenos Aires this use is more frequent.